Integrative analysis identifies TEAD4 as a universal prognostic biomarker in human cancers - Liu, Mohan; Song, Yang; Kang, Yue; Xue, Nan; Zhao, Jiuhan; Jin, Yi; Liu, Chang; Wang, Biao (Frontiers in Immunology, 2025)
IntroductionTEA domain transcription factor 4 (TEAD4), a key effector of the Hippo signaling pathway, has been increasingly associated with tumorigenesis and cancer progression. Despite its recognized role, comprehensive pan-cancer analyses of TEAD4 expression patterns, prognostic significance, and therapeutic implications remain scarce.MethodsWe conducted a systematic evaluation of TEAD4 across diverse tumor types using publicly available datasets, including TCGA. Analyses included gene expression profiling, prognostic correlation, functional enrichment, and drug sensitivity assessments. Additionally, in vitro assays were performed to validate the functional roles of TEAD4 in cancer cell behavior.ResultsTEAD4 was significantly overexpressed in multiple cancers and associated with unfavorable prognosis. Functional enrichment analyses implicated TEAD4 in oncogenic processes such as proliferation, metastasis, stemness maintenance, and immune regulation. In vitro experiments confirmed that TEAD4 promotes cancer cell proliferation, migration, and stem cell-like properties, while TEAD4 knockdown reversed these phenotypes. TEAD4 expression correlated with genomic instability, epigenetic alterations, and remodeling of the tumor microenvironment. Drug sensitivity analysis indicated that elevated TEAD4 levels were linked to resistance against several chemotherapeutic agents. Furthermore, a prognostic model based on TEAD4 target gene expression successfully stratified patients by survival risk.DiscussionOur findings highlight the multifaceted roles of TEAD4 in cancer biology, emphasizing its contribution to tumor progression, therapy resistance, and patient outcomes. The evidence supports TEAD4 as a promising prognostic biomarker and therapeutic target, offering new avenues for translational cancer research.